Modeling correction activities in the context of verification strategies. Issue 2 (19th November 2021) - Xu, Peng; Salado, Alejandro
Abstract: Correction activities (CAs), which can take the form of redesign, rework, or repair, are essential to system development. Whereas verification activities (VAs) provide information about the state of the system, CAs modify the state of the system to facilitate its correct operation. However, existing approaches to modeling and optimizing verification strategies take a simplistic approach to CAs. Specifically, CAs are modeled as an expected cost to achieve a desired confidence level after a VA has failed and are inherent to such VAs. In this paper, we present a modeling paradigm based on Bayesian networks (BNs) that captures the effects of different types of CAs. This modeling paradigm allows for the integration of verification and correction decisions (CDs) under a common framework. The modeling paradigm is illustrated in the notional case of a communication system.